Computational quest for understanding the role of astrocyte signaling in synaptic transmission and plasticity - De Pitta', Maurizio; Volman, Vladislav; Berry, Hugues; Parpura, Vladimir; Volterra, Andrea; Ben-Jacob, Eshel (Frontiers in Computational Neuroscience, 2012)
The complexity of the signaling network that underlies astrocyte-synapse interactions may seem discouraging when tackled from a theoretical perspective. Computational modeling is challenged by the fact that many details remain hitherto unknown and conventional approaches to describe synaptic function are unsuitable to explain experimental observations when astrocytic signaling is taken into account. Supported by experimental evidence is the possibility that astrocytes perform genuine information processing by means of their calcium signaling and are players in the physiological setting of the basal tone of synaptic transmission. Here we consider the plausibility of this scenario from a theoretical perspective, focusing on the modulation of synaptic release probability by the astrocyte and its implications on synaptic plasticity. The analysis of the signaling pathways underlying such modulation refines our notion of the tripartite synapse and has profound implications on our understanding of brain function.